2009
DOI: 10.1074/mcp.m900140-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cardiovascular Biomarkers in Patient Plasma by Targeted Mass Spectrometry and Stable Isotope Dilution

Abstract: Verification of candidate biomarkers requires specific assays to selectively detect and quantify target proteins in accessible biofluids. The primary objective of verification is to screen potential biomarkers to ensure that only the highest quality candidates from the discovery phase are taken forward into preclinical validation. Because antibody reagents for a clinical grade immunoassay often exist for a small number of candidates, alternative methodologies are required to credential new and unproven candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
250
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(263 citation statements)
references
References 25 publications
9
250
2
2
Order By: Relevance
“…Our analyses of the CPTAC protein spike data from two sites yielded CVs ranging from 3-21% with a median of 8.5%. These results also are consistent with previous evaluations of SID (2,3,7,8).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our analyses of the CPTAC protein spike data from two sites yielded CVs ranging from 3-21% with a median of 8.5%. These results also are consistent with previous evaluations of SID (2,3,7,8).…”
Section: Discussionsupporting
confidence: 83%
“…In practice, this approach has proven sensitive enough to apply to challenging protein quantitation problems. For example, proteins can be quantified at singledigit copy numbers in cells (6) and in plasma at levels approaching ng/ml (7,8). With antibody-based enrichment, LC-MRM-MS can achieve even greater sensitivity (9 -12).…”
mentioning
confidence: 99%
“…Kuzyk and coworkers developed a mixture of 45 peptide standards in EDTA‐plasma without affinity depletion or enrichment and found that 31 of the 45 are putative markers of cardiovascular disease 116. Keshishian and coworkers developed quantitative assays without immunoaffinity enrichment for six proteins of clinical relevance to cardiac injury ranging from 2 to 15 ng/ml and measured these proteins across three time points in six patients undergoing alcohol septal ablation for hypertrophic obstructive cardiomyopathy 117. Addona and coworkers used a combination of discovery and targeted proteomics in the context of planned myocardial infarction (PMI) for treatment of hypertrophic cardiomyopathy and myocardial infarction (MI) 118.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Over the past decade a number of papers have been published on the development of methods for the quantification of BNP by mass spectrometry (MS) [10,[12][13][14][15][16]. Issues including the very low concentration of BNP in plasma, the difficulties associated with measuring large intact peptides by MS and poor stability of BNP in plasma (half-life of 22.6 min) have however limited their further development for application in clinical laboratories.…”
Section: Introductionmentioning
confidence: 99%